One-pot oxidative desulfurization of fuels using dual-acidic deep eutectic solvents. (1st April 2020) - Liu, Wei; Li, Tenghui; Yu, Guojia; Wang, Jiangang; Zhou, Zhiyong; Ren, Zhongqi
Highlights: Dual-acidic DESs were prepared for one-pot oxidative desulfurization of fuels. l -Pyro/TFA showed both excellent catalytic and extractive characteristics. The sulfur removal rates of DBT, 4, 6-DMDBT and BT were up to 99.7%, 99.6% and 99.2%. l -Pyro/TFA showed good regeneration properties treated by washing with pure water. Abstract: Four dual-acidic deep eutectic solvents (DESs) were synthesized and investigated in an oxidative desulfurization (ODS) system using hydrogen peroxide as oxidant. l -Pyroglutamic acid/trifluoracetic acid (l -Pyro/TFA) was further investigated as the extractant and catalyst owing to its excellent properties for removing aromatic sulfur compounds. Hydrogen bond formation by l -Pyro/TFA was confirmed using 1 H NMR and infrared spectra. The factors affecting the desulfurization efficiency, such as the DES/model oil volume ratio (VDES /VOil ), reaction temperature, and H2 O2 /dibenzothiophene (DBT) molar ratio (n(H2 O2 )/n(DBT)), were explored. The sulfur removal rates of DBT, 4, 6-dimethyldibenzothiophene, and benzothiophene were up to 99.7%, 99.6%, and 99.2%, respectively, under the optimum conditions, which were VDES /Voil  = 1:20, n(H2 O2 )/n(DBT) = 3, and T = 60 °C. The ODS reaction followed first order kinetics through dynamic analysis. Furthermore, the desulfurization efficiency reached 98% after DES regeneration, achieved by simply washing with ultrapure water.